2022
DOI: 10.17755/esosder.1011832
|View full text |Cite
|
Sign up to set email alerts
|

Eği̇ti̇m Örgütleri̇nde İş Yaşaminda Yalnizlik İle Yaşam Doyumu İli̇şki̇si̇: İşle Bütünleşmeni̇n Araci Rolü

Abstract: Bu araĢtırmada; öğretmenlerin iĢ yaĢamında yalnızlık düzeyleri ile iĢle bütünleĢme ve yaĢam doyumu düzeyleri arasındaki iliĢkinin incelenmesi amaçlanmaktadır. Bu çalıĢma; nicel araĢtırma desenlerinden korelasyonel desen ile tasarlanmıĢtır. Siirt ilindeki ilkokullarda görev yapan öğretmenler, araĢtırmanın evrenini meydana getirmektedir. AraĢtırmanın örneklemi ise Siirt ilindeki 26 ilkokulda görev yapan 241 öğretmenden oluĢmaktadır. AraĢtırmada, seçkisiz örnekleme yöntemlerinden oransız küme örnekleme yöntemine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Teachers should have unique professional ethics and work values that do not disrupt their official duties (Toprakçı, Bozpolat & Buldur, 2010). In the literature, it is reported that the work values adopted by teachers will lead to exhibiting behaviors compatible with common values and goals in educational organizations, giving importance to the expectations of the school rather than individual expectations, exhibiting high-level performance in the preparation of learning environments, and conducting instructional practices that facilitate student learning, and thus increasing effectiveness and efficiency (Demir & Çobanoğlu, 2022;Tanatar & Alpaydın, 2019;Bozkurt & Doğan, 2013;Gökçen, 2021;Sağnak, 2005;Altaş, 2019). In this context, it can be argued that teachers can carry out more efficient and effective instructional activities thanks to their professional work values, and their trust and commitment to the school will be higher.…”
Section: The Relationship Between Work Values Work Performance and Et...mentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers should have unique professional ethics and work values that do not disrupt their official duties (Toprakçı, Bozpolat & Buldur, 2010). In the literature, it is reported that the work values adopted by teachers will lead to exhibiting behaviors compatible with common values and goals in educational organizations, giving importance to the expectations of the school rather than individual expectations, exhibiting high-level performance in the preparation of learning environments, and conducting instructional practices that facilitate student learning, and thus increasing effectiveness and efficiency (Demir & Çobanoğlu, 2022;Tanatar & Alpaydın, 2019;Bozkurt & Doğan, 2013;Gökçen, 2021;Sağnak, 2005;Altaş, 2019). In this context, it can be argued that teachers can carry out more efficient and effective instructional activities thanks to their professional work values, and their trust and commitment to the school will be higher.…”
Section: The Relationship Between Work Values Work Performance and Et...mentioning
confidence: 99%
“…Teachers' work values and qualifications related to their profession will not only shape the quality of education but also move their institutions one step further compared to their competitors (Troman & Raggl, 2008;Lin, 2007) and make the education and training process more efficient (Kaymak & Titrek, 2021). In this regard, it is extremely important to develop and improve teachers' understanding, attitudes and, accordingly, vocational-professional approach to the working conditions and school atmosphere in educational organizations (Bağçe, 2022;Ergül, 2009;Kayaalp & Özdemir, 2020;Demir & Çobanoğlu, 2022).…”
Section: Introductionmentioning
confidence: 99%